THE POTENTIAL OF THE IMPLEMENTATION OF DENGUE HEMORRHAGIC FEVER (DHF) PARTICIPATORY MAPPING TRAINING FOR LARVAE OBSERVER CADRES (JURU PEMANTAU JENTIK / JUMANTIK) - Lilik Zuhriyah; Yulia Dwi Setia (Universitas Brawijaya, 2020)
Jumantik plays a pivotal role in the control of Dengue Hemorrhagic Fever (DHF). Participatory mapping training can enhance its risk of transmission recognition. This research aims to identify the potential use of DHF risk factors participatory mapping training for Jumantik. This experimental research carried out from October 2013-January 2014 in four DHF highest prevalence regions in Malang. Mapping is based on data from Google Earth, DHF risk factors like homes, ovitrap sites, and larva-positive buildings, and the DHF prevalence over the past 6 months. The results indicate a variety of participant’s capacity to generate maps while the ability to analyze and plan was conspicuously absent. Qualitative data reveals there's an intention to map DHF individually by a few numbers of jumantik and primary healthcare staff. The conclusion is that this training prototype can be further adapted by accounting participant’s features, approaches, and capabilities as well as primary healthcare commitment for its continuity.